К вопросу о проблеме инновации высшего образования - Каминская, Т. С. (БНТУ, 2011)
This article is devoted to improve the quality of higher educational standards by the introduction of technology of innovative education. Different approaches are analyzed to understand the nature, the main purpose and the content of innovative education.